Letter (copy) : Manifesto - Citrine, Walter, 1887-1983
011-0072-001 WMC/WJB/AC/855 International 2nd July, 1937. The Secretary, Comité International de Coordination et d'Information pour l'Aide à l'Espagne Republicaine, 27, rue Jean-Dolent, PARIS XIVe Dear Sir, MANIFESTO. We have received a circular addressed to us from your organisation, stating that unless you receive instructions to the contrary you intend to place the signature of our General Council and its officers to a manifesto which has been passed by your Executive Committee. You will be aware that the British Trades Union Congress forms part of the International Federation of Trade Unions, which, in conjunction with the Labour and Socialist International, is dealing with all questions appertaining to the struggle in Spain. Our decisions can only be taken in collaboration with the other members of these International organisations, and we would suggest, therefore, that you address your letter to the International Federation of Trade Unions, whose headquarters are: 9, avenue d'Orsay, PARIS VIIe. Further, in view of these circumstances, we cannot authorise you to append the name of the British Trades Union Congress General Council, or that of any of its officers to the document you send for our consideration. Yours faithfully, General Secretary. 292/946/11/72